Effects of Dietary Supplementation of Pomegranate Peel with Xylanase on Egg Quality and Antioxidant Parameters in Laying Hens - Styliani Lioliopoulou; Georgios A. Papadopoulos; Ilias Giannenas; Konstantina Vasilopoulou; Clare Squires; Paschalis Fortomaris; Fani Th. Mantzouridou (MDPI AG, 2023)
Pomegranate contains bioactive compounds in all its parts. In this study, two levels of pomegranate peel byproduct (PPB) with or without the inclusion of xylanase enzyme were used to supplement laying hens' diet, in a 2 × 2 full factorial design. A total of 48 Isa brown laying hens were fed the following experimental diets for 8 weeks: T1 (2.5% PPB); T2 (2.5% PPB and xylanase); T3 (5% PPB); T4 (5% PPB and xylanase). Eggs collected were analyzed for egg quality parameters. Moreover, egg yolks were analyzed for Malondialdehyde content (MDA), fatty acid profile and total phenolic content. The T2 eggs showed enhanced yolk coloration and greater yolk total phenolic content. The T3 and T4 egg yolks showed lower MDA levels compared with T1, T2. Overall, results have shown that (a) xylanase inclusion affected egg yolk coloration and total phenolic content when combined with 2.5% PPB dietary supplementation; (b) dietary supplementation of 5% PPB resulted in eggs with reduced MDA levels.